Sexual Offender Recidivism Among a Population-Based Prison Sample. (April 2015) - Rettenberger, Martin; Briken, Peer; Turner, Daniel; Eher, Reinhard
The present study examines recidivism rates in sexual offenders using officially registered reconvictions in a representative data set of N = 1, 115 male sexual offenders from Austria. In general, results indicate that most sexual offenders do not reoffend sexually after release from prison. More detailed, within the first 5 years after release, the sexual recidivism rate was 6% for the total sample, 4% for the rapist subgroup, and 8% for the child molester subgroup. The findings confirmed previous studies about sex offender recidivism which have shown that first-time sexual offenders are significantly less likely to sexually reoffend than those with previous sexual convictions. With regard to the relationship between age and sexual recidivism, the results challenged the traditional assumption of a clear linear function between age and recidivism. Taken together, compared with previous studies, the recidivism rates found in the present investigation are substantially lower than previous research has indicated.